The mechanistic basis for interprotomer deglycosylation of antibodies by corynebacterial IgG-specific endoglycosidases - Diego E. Sastre; Stylianos Bournazos; Maros Huliciak; Barbara Ann C. Grace; E. Josephine Boder; Jonathan Du; Nazneen Sultana; Tala Azzam; Trenton J. Brown; Maria W. Flowers; Pete Lollar; Ting Xu; et al. (Nature Communications)
Abstract Corynebacterium diphtheriae clade species secrete single-domain endo-β-N-acetylglucosaminidases (ENGases) that specifically bind to human IgG antibodies and hydrolyze their N297-linked glycans. Here, we define the molecular mechanisms of IgG-specific deglycosylation for the entire family of corynebacterial IgG-specific ENGases, including but not limited to CU43 and CM49. By solving the crystal structure of CU43 in a 1:1 complex with the IgG1 Fc region, combined with targeted and saturation mutagenesis analysis and activity measurements using engineered antibodies, we establish an inter-protomeric mechanism of recognition and deglycosylation of IgG antibodies. Using in silico modeling, small-angle X-ray scattering and saturation mutagenesis we determine that CM49 uses a unique binding site on the Fc region, to process N297-linked glycans. Moreover, we demonstrate that CU43 treatment is highly effective in abrogating Fc effector functions in humanized mouse models, while preserving the neutralizing capacity of anti-influenza IgG antibodies, thereby conferring protection against lethal influenza challenge.